Análisis del material didáctico en el aprendizaje del idioma kichwa - Guambo Guanulema, Blanca Rebeca (2024)
The objective of the study was to analyze the didactic material in the learning of the Kichwa language among upper-basic students of the Intercultural Bilingual Educational Unit "Sangay." The purpose of this project was identify some resources that support student learning. The methodology had a mixed approach, which allowed the use of techniques and instruments that facilitate the observation, description, and collection of ideas from the studied population. The research techniques used included a survey for the independent variable (didactic material) and an observation sheet for the dependent variable (Kichwa language). The design was non-experimental and cross-sectional, supported by documentary and field research. The population consisted of 17 upper-basic students. As a result of this project, the need for certain students to identify specific resources, which are appropriately used and thus facilitate understanding, is highlighted. Among the conclusions, it is noted that although there are findings from this study, they will contribute significantly to more effective pedagogical practices, where their capacity to facilitate understanding and retention of knowledge, promote interest and motivation in the study of the language, and support the preservation and appreciation of Kichwa culture within the educational context is emphasized.